Occupational accidents with biological material at a university hospital (Research, Society and Development, 2022)
The objective of this study was to identify the occurrence and characteristics of occupational accidents with exposure to biological material among nursing workers at a clinic hospital. This is an exploratory research, with a quantitative approach and cross-sectional design, carried out in a university clinic hospital in Minas Gerais from 2008 to 2009. For data collection, an anonymous and self-administered instrument was developed. Data analysis was performed using descriptive and association statistics. Of the 322 professionals studied, 79 suffered accidents involving biological material, and nursing technicians (72.15%) were the most exposed, the main contaminating agent was blood (77.21%) during venipuncture procedures (35.4%) and the highest prevalence of accidents was observed in the afternoon shift. The high prevalence of work-related accidents with biological material in the nursing team was related to the long daily work hours, the overconfidence shown by the more experienced professionals and the non-adherence to biosafety standards.